Ending the War Between Humanity and Nature Rethinking Everything. - Lee, Patrick C. (Cambridge Scholars Publisher, 2020)
This book offers plausible explanations for people's puzzling unwillingness to address the human-nature interactions that have led us to the precipice that is climate change today. Humanity and nature are at war; the evidence is all around us: catastrophic weather events, rising sea levels, extinction of species, famine, wildfires, melting polar ice, millions of environmental refugees, and toxic pollution of air, water, and soil. The list goes on and on. What is causing this war, and how can it be stopped? Is this war an unintended consequence of economic and environmental imperatives pulling.